The Role of ASIC1a in Inflammatory Immune Diseases: A Potential Therapeutic Target - Wang, Yinghong; Hu, Xiaojie; Sun, Yancai; Huang, Yan (Frontiers in Pharmacology, 2022)
It is acknowledged that chronic inflammation is associated with a rise in extracellular proton concentrations. The acid-sensing ion channel 1a (ASIC1a) belongs to the extracellular H+-activated cation channel family. Recently, many studies have been conducted on ASIC1a and inflammatory immune diseases.Here,in this review,we will focus on the role of ASIC1a in several inflammatory immune diseases so as to provide new perspectives for clinical treatment.